Work Family Conflict And Work Family Enrichment Among Professional Women : A Malaysian Case - Sabil, Surena (Universiti Malaysia Sarawak (UNIMAS), 2011)
Participation of women in the workplace can be seen as a basis of excellence of future global competitiveness. Mainly because in Malaysia, women comprise 50% of the work force, whereby 70% of them are married working women. Such trend of married working women in Malaysia will become a common scenario in Malaysia. Hence, bringing more women into the workplace is not a choice but a necessity for both economic and global competition. Further Malaysia has a long way to go since female participant rate is much less compare with developed countries where the figures are more than 70%. However, the recent comments by CUEPACS, an organization that responsible for the welfare of public sector workers in Malaysia regarding their concern over the excess of women administrators in the public sector has created unrest among many dual work women. CUEPACS is worried about the commitment of women administrator at the workplace due their family responsibilities. Such concern on the negative implication of women’s involvement at work place on their family has been also been significantly emphasized by studies in the West and East. Thus the objective of the paper is to explore the relationship of work family conflict towards work family enrichment. The following study was conducted among professional women working in the public sector in the state of Sarawak, Malaysia. Both WFC and WFE used the nine-item work to family direction of the conflict and also the nine item work to family direction of the enrichment scale developed by Carlson et al. (2000) and Carlson et al. (2006). This study using sequential explanatory design involved survey and interview. The data was collected through questionnaires that were distributed personally to the respondent at their respective workplace, followed by in depth interview. Survey results indicated that there are significant relationship between work family conflict and work family enrichment, whereby lower WFC has positive implication towards work and their family. Managing role transition effectively and support from family has been identified as important factors in enhancing women’s productive participation in the labor force as well to create a balance between the work and family